Images of a changing frontier worldview in Eastern Cape art from Bushman rock art to 1875 - Cosser, Marijke (Rhodes University, Faculty of Humanities, Department of Fine Art, 1992)
A discussion of the concept of worldview shows that how an artist conceives the world in his images is governed by his worldview - an amalgam of the worldview of the group of which he is a part modified by his own ideas, beliefs, attitudes, perceptions and upbringing. The author proposes that studying an artist's work can reveal his, and hence his group's, worldview and thus the attitudes prevalent when the work was produced. A brief historical sketch of the Eastern Cape to 1834 introduces the various settlers in the area. Though no known examples of Black, Boer or Khoi pictorial art are extant, both the Bushmen and the British left such records. A short analysis of rock art shows how the worldview of the Bushman is inherent in their images which reflect man's world as seen with the "inner" eye of the spirit. In white settler art, the author submits that spatial relationships changed in response to a growing confidence as the "savage" land was "civilised" and that the position, pose and size of figures - and the inclusion or exclusion of certain groups - reflect socio-political changes. The two foremost nineteenth-century Eastern Cape artists, Thomas Baines and Frederick I'Ons, succeeded in capturing the atmosphere of Frontier life but are shown to interpret their surroundings through the rose-tinted spectacles of British Romanticism. They also reveal individuality in approach - Baines preferring expansive views while I'Ons's landscapes tend to be "closed-in", strictly following the coulisse scheme of Picturesque painting. Perhaps, the author postulates, such differences result from the very different environments, i.e. Norfolk and London, in which the two grew up. I'Ons is shown typically to use generalised landscapes as backdrops for his foreground figures, while comparing Baines's scenes with modern photographs shows that he adjusted the spacial elements of the topography as well as the temporal sequence of events to suit aesthetic considerations. Lithographed reports of his work contain even further adjustments. The author concludes that the use of Africana art as historical records must be treated with great caution.
Keywords: Art, San; Rock paintings -- South Africa; Art, -- South African -- 19th century; Art -- South Africa -- History; Painters -- South Africa